Impact of introduction of noninvasive prenatal testing on uptake of genetic testing in fetuses with central nervous system anomalies. (15th May 2019) - Al Toukhi, Samar; Chitayat, David; Keunen, Johannes; Roifman, Maian; Seaward, Gareth; Windrim, Rory; Ryan, Greg; Van Mieghem, Tim
Abstract: Objective: To evaluate the impact of introduction of noninvasive prenatal testing (NIPT) on the uptake of invasive testing in pregnancies complicated by fetal central nervous system (CNS) anomalies. Methods: Retrospective review of all singleton pregnancies complicated by fetal CNS anomalies seen at a single tertiary center between 2010 and 2017. Cases who had undergone invasive testing or NIPT prior to the diagnosis of the CNS anomaly were excluded. Cases were segregated according to whether they were seen prior to introduction of NIPT (group A, 2010‐2013) or thereafter (group B, 2014‐2017). We examined the rate of invasive and noninvasive genetic testing in each group. Results: We retrieved 500 cases: 308 (62%) were isolated CNS anomalies, and 192 (38%) had additional structural anomalies. In the total cohort, 165 women (33%) underwent expectant management with no further prenatal genetic testing, 166 (33%) had invasive testing, 52 (10%) had NIPT, and 117 pregnancies (23%) were terminated without further prenatal investigations. The introduction of NIPT significantly decreased the number of pregnancies having no testing (44% group A vs 22% in group B, p < .0001), particularly in the group presenting with isolated ventriculomegaly, but did not affect the uptake of invasive testing (34% vs 32%, respectively; p = .61 ) . NIPT would have missed 4% of pathogenic copy number variants (CNVs) in the group of cases with isolated brain anomalies and 11% of CNVs in cases with complex anomalies. Conclusions: Uptake of invasive prenatal testing in fetuses with brain anomalies was not affected by NIPT. However, the incidence of no genetic testing was significantly reduced. NIPT was a suboptimal testing strategy in this population as it missed a significant number of subchromosomal genetic anomalies. Abstract : What's already known about this topic? NIPT is a screening test with high sensitivity for common chromosomal anomalies. With the introduction of NIPT, prenatal invasive diagnostic testing has been decreased. What does this study add? Invasive prenatal testing for fetuses with central nervous system anomalies at our institution has not been affected with the introduction of NIPT. For fetuses with central nervous system anomalies, NIPT will miss a significant number of submicroscopic chromosomal abnormalities.